The Effect of Motivation and Discipline on Employee Performance at PT. Keb Hana Bank Serpong Branch Office - Muhammad Ramdhan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
This study aims to determine the effect of motivation and discipline on employee performance at PT. Keb Hana Bank Serpong Branch Office. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that motivation has a significant effect on employee performance by 46.5%, hypothesis testing is obtained t count > t table or (7.965 > 1.993). Discipline has a significant effect on employee performance by 42.7%; hypothesis testing is obtained t count > t table or (7.380 > 1.993). Motivation and discipline simultaneously have a significant effect on employee performance with the regression equation Y = 6.755 + 0.416X1 + 0.430X2. The influence contribution is 61.1%, hypothesis testing is obtained by F arithmetic > F table or (56.517 > 2.730).